(untitled) (International Journal of Medicine & Health Research (IJMHR) (ISSN 2395-3586), 2024)
Introduction: The goal of this work was to determine the place of the deficiency-related etiology in Pancytopenia, facilitation of the diagnosis and the definition of the epidemiological, clinical and paraclinical characteristics of deficiency-related Pancytopenia. Methodology: It is a retrospective study of 112 Pancytopenia cases of which 34 were Deficiency-related Pancytopenia taken from a data taken from a period of 5 years (2006-2010) from the Hematology Laboratory of the Mohammed V Teaching Military Hospital Rabat. Results: 112 Pancytopenia cases were found. The result from a comparison between 2 groups of patients of medium age with or without etiological deficiency-related Pancytopenia by the “Student Test” was t = 0.001070744<0.025 and the comparison of the parameters of the Hemogram by the ANOVA Test gave the following values: F= 0.41, p= 0.565 greater than alpha= 0.05 for a limit of 5%. For the 34 cases of deficiency-related Pancytopenia studied, 11 were women and the rest men. The medium age was 48.47 years. The medium level of Hb was 6.11 g/dl. Leukocyte and platelet Numeration Media were respectively 2.55 g/l and 58.78 g/l Discussion: The etiology deficiency-related is the principal cause of Pancytopenia in the department of Hematology of the Mohammed V Teaching Military Hospital Rabat. This diagnosis demands the use of myelogram and or the determination of the quantity of vitamins or the use of therapeutic tests. The epidemiological, clinical and para-clinical characteristics are similar to those found in literature. Conclusion: We observed the need for early diagnosis of vitamin deficiency (Vit B12 and Vit B9) coupled with the systemization of preventive measures for all persons at high risk. It is however primordial for regular follow-ups of the progression over a long period of time of patients under treatment at the aim of correcting the deficiency-related Pancytopenia